PROTECTIVE EFFECTS OF DIPEPTIDYL PEPTIDASE-4 INHIBITORS ON PROGRESSION OF DIABETIC RETINOPATHY IN PATIENTS WITH TYPE 2 DIABETES. Issue 12 (December 2016) - Chung, Yoo-Ri; Park, Sung Wook; Kim, Jong Wan; Kim, Jeong Hun; Lee, Kihwang
Abstract : Purpose: To investigate the effects of dipeptidyl peptidase-4 (DPP4) inhibitors on the progression of diabetic retinopathy (DR) in patients with Type 2 diabetes based on the DR severity scale. Methods: The medical records of 82 patients with Type 2 diabetes enrolled from 2005 to 2015 were retrospectively reviewed. Fundus photographs were graded using Early Treatment Diabetic Retinopathy Study methods. The associations between baseline risk factors and progression of DR were investigated. Results: Seven of 28 patients treated with DPP4 inhibitors and 26 of 54 treated with other hypoglycemic agents showed progression of retinopathy, defined as one or more steps on the Early Treatment Diabetic Retinopathy Study scale ( P = 0.043). Only treatment with DPP4 inhibitors significantly reduced the progression of DR in patients after propensity score matching ( P = 0.009). Treatment with DPP4 inhibitors was associated with a lower risk of DR progression ( P = 0.011). Conclusion: Treatment with DPP4 inhibitors was the independent protective factor against the progression of DR, aside from improving glycemic control. This is the first study to show the benefits of DPP4 inhibitors in reducing DR progression, and provides encouraging preliminary data for further evaluation of DPP4 inhibitors in the progression of DR in a randomized, double-blind, placebo-controlled trial. Abstract : This study showed that treatment with dipeptidyl peptidase-4 inhibitors was associated with a reduction of diabetic retinopathy progression in patients with Type 2 diabetes. This protective effect of dipeptidyl peptidase-4 inhibitors was independent of their glucose-lowering effects. Systemic treatment with dipeptidyl peptidase-4 inhibitors of patients with Type 2 diabetes should be considered to prevent diabetic retinopathy progression.